Formulation Development and Evaluation of Gastro Retentive Floating Drug Delivery System for Novel Fluoroquinolone using Natural and Semisynthetic Polymers: Formulation development and evaluation of Moxifloxacin. HCl gastroretentive floating tablets - Gunda, Raghavendra Kumar; Vijayalakshmi, A. (Iranian Journal of Pharmaceutical Sciences, 2020)
The purpose of present research work is to develop gastro retentive formulation for Moxifloxacin using various release retardants. Moxifloxacin, that is a novel synthetic fluoro quinolone, is an iantibacterial agent. Floating tablets of Moxifloxacin. HCl were prepared using variable amounts of HPMCK4M, HPMCK15M and HPMCK100M with effervescent mixtures by direct compression technique. Totally 9 formulations were designed, prepared and are evaluated for various pharmacopoeial tests like uniformity of weight, thickness,Hardness, friability, floating lag time, Total floating time. Drug release profiles of formulation trails subjected to kinetic modeling. Parameters like correlation coefficient(r), slope (b), intercept (a) were determined. The results reveal that floating lag time decreases with decreased viscosity of polymer composites. According to SUPAC guidelines formulation (F4) containing 12.5% HPMCK15M was found to be most identical formulation (similarity factor f2= 70.997, dissimilarity factor f1= 6.007 to marketed product (AVELOX). Trail F4 drug release found to be first order kinetics, Non-Fickian Diffusion Anomalous Transport. (n= 1.065).